2012
DOI: 10.1111/j.1464-410x.2012.10933.x
|View full text |Cite
|
Sign up to set email alerts
|

A biopsy simulation study to assess the accuracy of several transrectal ultrasonography (TRUS)‐biopsy strategies compared with template prostate mapping biopsies in patients who have undergone radical prostatectomy

Abstract: Study Type – Diagnostic (validating cohort) Level of Evidence 1b What's known on the subject? and What does the study add? Transrectal ultrasonography (TRUS)‐guided biopsies can miss prostate cancer and misclassify risk in a diagnostic setting; the exact extent to which it does so in a repeat biopsy strategy in men with low–intermediate risk prostate cancer is unknown. A simulation study of different biopsy strategies showed that repeat 12‐core TRUS biopsy performs poorly. Adding anterior sampling improves on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 34 publications
(30 reference statements)
0
44
1
2
Order By: Relevance
“…All patients underwent an additional TRUS-GB during the same biopsy session. Gleason grading was measured by two different methods: the conventional Gleason score (Berg et al 2011;McKenney et al 2011) and, more importantly, by the sampling error of undirected systematic TRUS-GB (Hu et al 2012). Improved prediction of the final prostatectomy Gleason grading would help to better assess the patient's risk, and the choice of treatment options could be more easily determined.…”
Section: Introductionmentioning
confidence: 99%
“…All patients underwent an additional TRUS-GB during the same biopsy session. Gleason grading was measured by two different methods: the conventional Gleason score (Berg et al 2011;McKenney et al 2011) and, more importantly, by the sampling error of undirected systematic TRUS-GB (Hu et al 2012). Improved prediction of the final prostatectomy Gleason grading would help to better assess the patient's risk, and the choice of treatment options could be more easily determined.…”
Section: Introductionmentioning
confidence: 99%
“…20,23,24 TTMB has been shown to closely correlate with whole-mount radical prostatectomy pathology in identifying high-grade cancer, 23 which also reinforces earlier simulation studies. 25 To select patients best suited for AS, we evaluated whether TTMB would indentify differences in AS eligibility between very-low-risk (Gleason score r6, r2 positive biopsies, PSA density <0.15, and r50% involvement on any core) and low-risk (Gleason score r6, PSA r10 ng/mL, and clinical stage T1c/T2a, excluding those who qualify for verylow-risk assignment) patients.…”
mentioning
confidence: 99%
“…TRUS-guided biopsies often fail to detect cancerous lesions, misclassify the cancer risk, and have been found to have sensitivity for detection as low as 60% [7, 11]. A study by Ouzzane, et al found up to 46% of 12-core biopsies in their trial had missed anteriorly located cancerous lesions [12-13].…”
Section: Reviewmentioning
confidence: 99%
“…A study by Ouzzane, et al found up to 46% of 12-core biopsies in their trial had missed anteriorly located cancerous lesions [12-13]. Hu, et al determined that transperineal prostate mapping (TPM) was more accurate versus five traditional TRUS-guided strategies at detecting and excluding lesions of tumor volume thresholds of 0.2 mL and 0.5 mL [11]. Additionally, TRUS-biopsy failed to detect 30-40% of lesions > 0.2 mL compared to 5% missed in TPM [11].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation